Motivation to learn and employability of Vocational High School students - Fatwa Tentama; Ghazi Arridha (Journal of Education and Learning (EduLearn), 2020)
Motivation to learn is one of the factors that can play a role in determining student employability. This study aimed to empirically test the role of motivation to learn on student employability. The population in this study were all grade twelve students in Vocational High School 1 Dlingo Bantul Yogyakarta, which is as many as 110 students. The sample in this study was 54 grade twelve students of Vocational High School 1 Dlingo Bantul, which consisted of two classes namely fashion and wood craft classes. The selection of the research sample was made by randomization using the cluster random sampling technique. Data collection was carried out by using the employability scale and motivation to learn scale. Data analysis was conducted using Pearson product-moment analysis technique. The analysis result shows that the magnitude of the correlation coefficient (r) between motivation to learn and employability was 0.747, p = 0.000 (p less than 0.01). This finding indicates that there is a very significant positive correlation between motivation to learn and student employability. Motivation to learn contributes as large as 55.8 percent of employability. Thus, motivation to learn does contribute to explaining the level of employability of Vocational High School students.